Politik Hukum Investasi Pertambangan di Indonesia - Rizqiani Purwaningtiyas R; Diajeng Dwi Oktaverina; Bhim Prakoso (Lembaga Pengembangan Kinerja Dosen, 2024)
This article discusses the dynamics of the development of mining management policies in Indonesia. Where mining activities in Indonesia itself have been going on for a long time. The study of this article shows mining regulatory policies in Indonesia to date, which have experienced many ups and downs in several regions of Indonesia. Starting from the licensing system, utilization of natural resources, policies towards mine workers and several other things, both national and international companies. The various dynamics of these developments show that mineral and coal mining is always seen as a strategic commodity economic center so it is worth fighting over, especially Indonesia which has a lot of natural resources whether it was once by domestic or foreign entrepreneurs and even recently by the central and regional governments, and the law was then held to support these goals.